E-Learning as a Center for Educational Innovation: an Evolution Study, Comparison of Implementation (School vs. University), and Strategic Recommendation at Wiralodra University - Cantika Revaliani Putri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article presents a comprehensive analysis of the role of e-learning as a key pillar of education system transformation in the digital era. The study begins by reviewing the evolution of e-learning from computer-based instruction systems (PLATO) to web-based Learning Management System (LMS) platforms and cloud computing. The accelerated adoption of e-learning, particularly post-COVID-19 pandemic, underscores its role in increasing the flexibility, efficiency, and accessibility of global education. A comparative analysis is conducted of e-learning implementation at the school and higher education levels, with the key finding that implementation in higher education must focus on fostering student self-regulated learning and critical thinking, in contrast to the basic focus at the school level. Despite offering great potential, the effectiveness of e-learning is hampered by serious challenges, particularly the digital divide (limited infrastructure and internet access) and online pedagogical issues (lack of interaction and learning motivation). It concludes that to optimize the quality of education, particularly at Wiralodra University, an implementation strategy is needed that focuses on strengthening inclusive infrastructure, intensive training for lecturers in online pedagogy, and the adoption of advanced technologies (such as Learning Analytics and VR/AR). These strategic steps are essential for creating an inclusive, effective, and competitive learning system.